2020
DOI: 10.1016/j.mayocpiqo.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in Racial Disparities in Health and Coronavirus Disease-2019 (COVID-19) Mortality

Abstract: Objective To evaluate the race-stratified state-level prevalence of health determinants and the racial disparities in coronavirus disease-2019 (COVID-19) cumulative incidence and mortality in the United States. Patients and Methods Age-adjusted race-stratified prevalence of comorbidities (hypertension, diabetes, dyslipidemia, obesity), preexisting medical conditions (pulmonary disease, heart disease, stroke, kidney disease, malignancy), poor health behaviors (smoking, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
0
28
0
1
Order By: Relevance
“…The COVID-19 pandemic has placed a disproportionate burden of morbidity and mortality on the Black and Hispanic populations [ 21 ], which is similar to previous viral pandemics [ 22 – 24 ]. Parcha et al [ 25 ] studied geographic variation and racial disparities in COVID-19 and demonstrated a threefold higher cumulative incidence rate (per 100,000) in Blacks compared with Whites, with a twofold higher crude mortality rate. In both the ICH-COVID and SAH-COVID comparisons, we found higher proportions of Blacks, Asians, and Hispanics than in the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has placed a disproportionate burden of morbidity and mortality on the Black and Hispanic populations [ 21 ], which is similar to previous viral pandemics [ 22 – 24 ]. Parcha et al [ 25 ] studied geographic variation and racial disparities in COVID-19 and demonstrated a threefold higher cumulative incidence rate (per 100,000) in Blacks compared with Whites, with a twofold higher crude mortality rate. In both the ICH-COVID and SAH-COVID comparisons, we found higher proportions of Blacks, Asians, and Hispanics than in the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Racial and ethnic disparities in outcomes associated with COVID-19 in the U.S. have been the subject of widespread concern and societal discourse. Characterizing racial/ethnic disparities in COVID-19 outcomes is an active area of scientific research [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and quantifying racial/ethnic disparities in the COVID-19 mortality burden has been a particular area of focus. For example, the Color of Coronavirus project of the American Public Media Research Lab [ 32 ] tracks COVID-19 death counts by race/ethnicity in each state, providing analyses and extended commentary on mortality rates by race/ethnicity and comparisons between the percentage of total deaths and the percent population share by race/ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings of variation of caseload across facilities is analogous to reports of geographic heterogeneity in disease prevalence. 22 For example, a serological survey from Spain reported substantial geographical variation, with higher prevalence near Madrid (>10%) and lower prevalence in coastal areas (<3%). 23 A study from the USA reported higher COVID-19 mortality in rural versus urban communities; however, that study was limited to county-level (not patient level) data.…”
Section: Discussionmentioning
confidence: 99%